Music, dance and festival among the Waiapi Indians of Brazil [videorecording] (Bloomington, In. Indiana University Audio-visual Center, 1992)
Examines five Waiapi Indian festivals and shows the importance of "manioc beer" in the festivals, the variety of musical instruments and songs, and how Waiapi identity and societal order are reinforced by these communal celebrations.
Keywords: Oyampi Indians; Festivals -- Brazil; Oyampi Indians -- Music; Music